Method for preparing high-temperature stable Fe2C by using mechanical ball milling method

By optimizing the ball mill parameters by using ultra-long-term mechanical ball milling method under an inert atmosphere, the single-phase Fe2C is directly synthesized, the problem of structural instability at high temperature is solved, high purity and high temperature stability are achieved, and it is suitable for high-temperature catalytic applications.

CN120247025APending Publication Date: 2025-07-04SYNFUELS CHINA INNER MONGOLIA CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510393526.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2025-07-04

AI Technical Summary

Technical Problem

The prior art is difficult to maintain the structural stability of Fe2C under high temperature conditions, resulting in limited application of its high temperature catalytic environment, and traditional preparation methods have problems with impurity doping and thermodynamic instability.

Method used

Fe2C is prepared under an inert atmosphere by using ultra-long mechanical ball milling method. By optimizing the ball milling time, rotation speed and ball material ratio, the iron source and carbon source are directly synthesized into single-phase Fe2C to avoid oxidation and impurities incorporation, and ensure high temperature stability.

Benefits of technology

The prepared Fe2C still maintains a stable phase structure above 400°C without phase change, significantly improving the purity and thermal stability of the material, and is suitable for high-temperature catalytic environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120247025A_ABST
    Figure CN120247025A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method for synthesizing a Fe2C iron carbide catalyst with high purity and excellent thermal stability by utilizing a mechanical ball milling method. According to the method, long-time mechanical ball milling is carried out in an inert atmosphere, and single-phase Fe2C is successfully prepared. According to the method disclosed by the invention, the preparation of high-purity Fe2C can be realized under a large-scale production condition, and the problems of impurity doping, thermodynamic instability and the like existing in an iron carbide preparation method (such as gas-phase synthesis and liquid-phase thermal decomposition) in the prior art are solved. In addition, the Fe2C synthesized by the method is at high temperature (gt; the structure is kept stable at the temperature of 400 DEG C, phase change is avoided, and the material is obviously superior to Fe2C materials reported in existing literatures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of material preparation, and particularly to a method for preparing a high-purity and thermally stable iron carbide catalyst Fe2C by mechanical ball milling method. Background Art

[0002] Iron carbide (Fe-C) has been widely used in the fields of magnetic materials, catalysts, and energy conversion due to its unique magnetic properties, catalytic activity, and chemical stability. Among them, Fe2C has attracted particular attention in reactions such as Fischer-Tropsch synthesis and ammonia synthesis due to its special crystal structure and excellent catalytic performance. However, existing research on Fe2C mainly focuses on low-temperature preparation and performance characterization, and relatively little attention has been paid to its high-temperature stability and thermodynamic phase transformation law. In addition, existing preparation methods (such as gas-phase synthesis, liquid-phase thermal decomposition, and solid-phase carbonization) still have certain limitations in improving the purity of the product and adapting to high-temperature catalytic environments.

[0003] For example, Chinese Patent CN110339849B prepared pure-phase ε / ε’Fe2C by optimizing the H2 / CO ratio and carbonization temperature, and maintained high stability at 250°C, but did not verify the structural integrity of this phase at higher temperatures. Another literature "Synthesis of Iron-Carbide Nanoparticles: Identification of the Active Phase and Mechanism of Fe-Based Fischer–Tropsch Synthesis (CCS Chem. 2020, 2, 2712)" reported the synthesis of Fe2C by thermal decomposition of iron carbonyl. However, the Fe2C synthesized by this method undergoes a phase change above 270°C, limiting its application under high-temperature conditions. Furthermore, existing technologies still lack effective solutions for the thermodynamic stability of Fe2C in high-temperature environments. Existing literature and patents (such as Chinese Patent CN110339849B) have pointed out that Fe2C is prone to phase transformation into Fe5C2 or Fe3C in the range of 250-300°C, restricting its application in high-temperature catalytic environments.

[0004] In view of the above problems, the present invention proposes a method for preparing high-purity and thermally stable Fe2C by ultra-long mechanical ball milling (300 - 400 hours). Compared with traditional liquid-phase thermal decomposition methods and gas-phase synthesis methods, this method does not require additional element addition, has a relatively simple process, and does not rely on high-temperature gas-phase equipment; compared with conventional ball milling methods, the present invention has systematically optimized the ball milling time and process parameters, significantly improving the crystallinity of Fe2C. More importantly, in-situ XRD studies have shown that the Fe2C prepared by the present invention can still maintain a stable phase structure above 400 °C without phase transformation, which is significantly better than similar materials reported in the literature that undergo phase transformation in the range of 250 - 300 °C. In addition, compared with the method for preparing boron-containing Fe7C3 catalysts by ball milling disclosed in Chinese Patent CN116984008A, the present invention can directly obtain high-purity Fe2C without adding boron element externally; meanwhile, this patent only explores the preparation conditions for single-phase Fe7C3 and does not involve the feasibility and high-temperature stability of ball milling preparation of Fe2C or other iron carbides. Summary of the Invention

[0005] The present invention provides a method for preparing a single-phase Fe2C material. In an inert gas environment, an iron source material and a carbon source material are placed in a ball milling tank filled with inert gas, and a single-phase Fe2C material is synthesized in one step by mechanical ball milling. The method of the present invention has simple steps, high repeatability, can prepare Fe2C materials in large quantities, and has high purity.

[0006] In order to achieve the above object, the present invention provides a method for preparing Fe2C by mechanical ball milling, including the following steps:

[0007] (1) Under the protection of an inert atmosphere, a carbon source material and an iron source material are placed in a ball milling tank in a certain proportion. At the same time, mechanical grinding balls of a certain size and mass are placed in the ball milling tank. The sealing cover of the ball milling tank is fixed to the ball milling tank and sealed tightly;

[0008] (2) The ball milling tank filled with the sample is placed in a mechanical ball mill, fixed in the corresponding position, the hatch cover of the ball mill is closed, the specific parameters of the mechanical ball mill are set, and then mechanical ball milling is carried out;

[0009] (3) After the mechanical ball milling is completed, the ball milling tank is taken out, opened under the protection of an inert atmosphere, the grinding balls and the product are separated using a standard sieve, the tank wall is scraped clean with a spoon, and the collected black solid powder is the Fe2C material.

[0010] In the above preparation method step (1), the inert atmosphere is one or more of argon atmosphere, helium atmosphere or nitrogen atmosphere.

[0011] In step (1) of the above preparation method, the carbon source material is one or more of nano-carbon powder, nano-graphite, and graphene; the iron source material is one or more of commercial nano-iron powder and metal iron powder obtained by hydrogen-reducing nano-scale iron oxide.

[0012] In step (1) of the above preparation method, the molar ratio of iron to carbon in the iron source material and the carbon source material is 2:1 to 0.5:1; preferably 2:1, 1.95:1, 1.9:1, 1.8:1, 1.7:1, 1.6:1, 1.5:1, 1.4:1, 1.3:1, 1.2:1, 1:1, 0.9:1, 0.8:1, 0.7:1, 0.6:1, 0.5:1, and more preferably 2:1 to 1:1. An excess of carbon powder is beneficial for the formation of Fe2C.

[0013] In step (1) of the above preparation method, the particle size range of the iron source material and the carbon source material is 20 - 100 nm, preferably 50 - 80 nm.

[0014] In step (1) of the above preparation method, the components of the ball milling tank and the balls are zirconia. The volume of the ball milling tank is 30 - 100 ml, preferably 30 - 60 ml, and more preferably 45 ml; the diameter of the balls is 2 - 5 mm, preferably 3 - 4 mm.

[0015] The mass ratio of the grinding balls to the raw materials (referred to as the ball-to-material ratio) is 15 - 35, preferably 15, 20, 25, 30, 35, and more preferably 20 - 30.

[0016] In step (1) of the above preparation method, the mass of the grinding balls is 50 - 80 g, preferably 55 - 65 g.

[0017] In step (2) of the above preparation method, the grinding tank and the planetary disk in the ball mill rotate in opposite directions, and the transmission ratio of the planetary disk / grinding tank is I = 1:2.

[0018] In step (2) of the above preparation method, the set parameters of the ball mill are: the rotational speed of the planetary disk is 200 - 400 r / min, preferably 300 r / min; the rotational speed of the grinding tank is 500 - 700 r / min, preferably 600 r / min. The ball milling time for one cycle is 20 - 40 min, preferably 30 min; the pause time between each cycle is 5 - 15 min, preferably 10 min; the number of ball milling cycles is 500 - 800, preferably 550 - 640; the total ball milling time is 200 - 500 h, preferably 270 - 400 h, and more preferably 290 - 350 h; the ball milling mode is reverse rotation.

[0019] In step (3) of the above preparation method, after the ball milling is completed, the ball milling tank is taken out, and after it cools naturally, the pressure is released to take the material.

[0020] In step (3) of the above preparation method, the inert atmosphere is one or more of an argon atmosphere, a helium atmosphere, or a nitrogen atmosphere.

[0021] In step (3) of the above preparation method, the standard sieve mesh number is 60 to 150 meshes, preferably 80 meshes.

[0022] The present invention also provides an Fe₂C material prepared according to the above method.

[0023] Compared with the prior art, the present invention has the following advantages:

[0024] (1) The present invention prepares the Fe₂C material in an inert gas environment, avoiding the oxidation of Fe₂C by air.

[0025] (2) The present invention directly synthesizes the carbon source and the iron source into the Fe₂C material, avoiding the incorporation of other elemental impurities during the intermediate process.

[0026] (3) The present invention uses the mechanical ball milling method to prepare the material, which can prepare a large batch of Fe₂C materials at one time. The preparation scheme is simple and has high repeatability.

[0027] (4) The present invention has explored for the first time the ball milling preparation conditions of Fe₂C and prepared the Fe₂C material by using the high-energy ball milling method.

[0028] (5) The Fe₂C material prepared by the present invention has high purity and is a single-phase Fe₂C material. Description of the Drawings

[0029] Figure 1 It is the XRD pattern of the Fe₂C material prepared in Example 1.

[0030] Figure 2 It is the MES pattern of the Fe₂C material prepared in Example 1.

[0031] Figure 3 It is the XRD pattern of the Fe₂C materials prepared in Comparative Examples 1-3.

[0032] Figure 4 It is the XRD pattern before and after the Fe₂C reaction prepared in Example 1.

[0033] Figure 5 It is the in-situ XRD pattern of the Fe₂C prepared in Example 1. Detailed Embodiments

[0034] The present invention will be further described in detail below in conjunction with the specific embodiments. The examples given are only for clarifying the present invention and not for limiting the scope of the present invention.

[0035] Unless otherwise specified, the experimental methods in the following examples are all conventional methods.

[0036] Unless otherwise specified, the materials, reagents, etc. used in the following examples are all commercially available.

[0037] Example 1: Preparation of Fe2C

[0038] Weigh 60.8 g of grinding balls (zirconia material, 3 mm in diameter) using an electronic balance, put them into a 45 mL ball mill jar with a zirconia liner, and place the ball mill jar into a glove box filled with a nitrogen atmosphere. Weigh 2.5 g of nano iron powder (average grain size 50 nm) and 0.5377 g of nano graphite (average grain size 80 nm) (the molar ratio of iron to carbon is 1:1) in the glove box, put them into the ball mill jar together with the grinding balls (the ball-to-material ratio is 20), seal the lid, take out the ball mill jar and put it into a ball mill. Set the ball milling parameters: the rotation speed of the planetary disk is 300 r / min, the rotation speed of the ball mill jar is 600 r / min, the ball milling mode is reverse, one cycle of ball milling is 30 min, and there is a 10 min pause between each cycle. A total of 608 cycles of ball milling are carried out. After the ball milling is completed, take out the ball mill jar, wait for it to cool naturally, take out the product in the glove box, separate the grinding balls and the powder using an 80-mesh sieve, and scrape the inner wall of the jar with a spoon to collect the obtained black powder.

[0039] For the characterization results of the product obtained in Example 1, see Figures 1 - 2 , and the Mössbauer spectrum parameters are shown in Table 1. From the above characterization results, it can be seen that the powder product is a single-phase Fe2C material.

[0040] Table 1

[0041] Phase asceription Area(%) IS(mm / s) QS(mm / s) H(kOe) <![CDATA[Fe2C(I)]]> 26.6 0.35 0.32 167 <![CDATA[Fe2C(II)]]> 20.7 0.5 0.17 258 <![CDATA[Fe2C(III)]]> 49.2 0.10 -0.11 174 <![CDATA[Fe 3+ (spm)]]> 3.5 0.23 1.14

[0042] From Figure 2 and the Mössbauer spectrum results in Table 1, it can be seen that the sample prepared by ball milling in Example 1 of the present invention conforms to the Mössbauer spectrum parameter characteristics of pure-phase Fe2C, which can prove that the prepared sample is single-phase Fe2C.

[0043] Comparative Example 1: Preparation of Fe2C

[0044] Except that the ball milling time, rotation speed, type and mass of the grinding balls are the same as those in Example 1, this comparative example changes the amount of nano graphite used to make the molar ratio of iron to carbon deviate from the theoretical ratio of Fe2C. The specific operation is as follows: In a nitrogen glove box, weigh 2.5 g of nano iron powder and 0.215 g of nano graphite (the molar ratio of iron to carbon is 2:0.8), and place them together with 54.3 g of zirconia (the ball-to-material ratio is 20) grinding balls in a ball mill jar. Take out the product after the ball milling is completed. For the characterization results of the product obtained in Comparative Example 1, see Figure 3, an excessive amount of free iron and other iron carbides (such as Fe7C3) appeared in the product, and single-phase Fe2C was not formed. The above results indicate that when the iron-carbon ratio is insufficient, high-purity Fe2C cannot be obtained.

[0045] Except that the molar ratio of iron to carbon is the same as that in Example 1, in this comparative example, the amount of grinding balls used was changed (the ball-to-material ratio was 10), that is, the zirconia grinding balls were reduced from 60.8 g to 30.377 g, significantly reducing the ball-to-material ratio; the remaining conditions including the ball milling speed and the total time were the same as those in Example 1. After ball milling was completed, the product powder was collected. The characterization results of the product obtained in Comparative Example 2 are shown in Figure 3 , only metallic iron was present in the product, and the Fe2C phase could not be obtained. This indicates that when the ball-to-material ratio is insufficient, the effective energy transfer of mechanical ball milling to iron powder and graphite is limited, and it is difficult to achieve the formation of Fe2C.

[0046] Comparative Example 3: Preparation of Fe2C

[0047] Except that the molar ratio of iron to carbon is the same as that in Example 1, in this comparative example, the amount of grinding balls used was changed (the ball-to-material ratio was 40), that is, the zirconia grinding balls were increased from 60.8 g to 121.6 g, significantly increasing the ball-to-material ratio; the remaining conditions including the ball milling speed and the total time were the same as those in Example 1. After ball milling was completed, the product powder was collected. The characterization results of the product obtained in Comparative Example 3 are shown in Figure 3 , the iron carbide Fe7C3 appeared in the product, and single-phase Fe2C was not formed. The above results indicate that when the ball-to-material ratio is too large, high-purity Fe2C cannot be obtained.

[0048] Example 2:

[0049] The catalyst was placed in a fixed bed for evaluation. The activation conditions were as follows: the reaction atmosphere was syngas with H2:CO = 2:1, the space velocity was 15000 ml·g -1 ·h -1 , the activation temperature was 220 °C, the pressure was 0.1 MPa, and the activation time was 5 h. Then the pressure was boosted to 2 MPa, the temperature was set to 220 - 280 °C, and the space velocity was set to 30000 ml·g -1 ·h -1 . The catalyst loading was 50 mg. The product after the reaction was analyzed by gas chromatography, and the evaluation data for 24 h of reaction are shown in Figure 4 , Table 2.

[0050] Table 2

[0051] It can be seen from the evaluation data in Table 2 that by carrying out the Fischer-Tropsch synthesis reaction on Fe2C at different temperatures, it was found that as the reaction temperature increased, the CO conversion rate continuously increased, and the selectivities of CO2 and CH4 gradually increased, C5+ The selectivity continuously decreases. The catalytic activity of Fe2C reacted at 280 °C is the highest, and the CO conversion rate is the largest. The Fe2C catalyst after the reaction at 280 °C was characterized by XRD. As Figure 4 shown, it was found that the Fe2C phase remained unchanged.

[0052] An in-situ XRD experiment was conducted on the prepared Fe2C. As Figure 5 shown, it was found that Fe2C began to phase-transform and decompose into metallic iron at 500 °C, indicating that the Fe2C material prepared by the ball milling method has strong thermal stability.

[0053] The above are only the preferred embodiments of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the method of the present invention, several improvements and supplements can be made, and these improvements and supplements should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing Fe₂C by mechanical ball milling, comprising the following steps: (1) Under the protection of an inert atmosphere, put the carbon source material and the iron source material into a ball milling tank in a certain proportion. At the same time, put mechanical grinding balls of a certain size and mass into the ball milling tank. Fix the sealing cover of the ball milling tank to the ball milling tank and seal it tightly; (2) Put the ball milling tank filled with the sample into a mechanical ball mill, fix it in the corresponding position, close the hatch of the ball mill, set the specific parameters of the mechanical ball mill, and then carry out mechanical ball milling; (3) After the mechanical ball milling is completed, take out the ball milling tank, open the ball milling tank under the protection of an inert atmosphere, use a standard sieve to separate the grinding balls from the product, scrape the tank wall clean with a spoon, and collect the obtained black solid powder, which is the Fe₂C material.

2. The method according to claim 1, wherein: In step (1), the inert atmosphere is one or more of an argon atmosphere, a helium atmosphere or a nitrogen atmosphere.

3. The method according to claim 1, characterized in that: In step (1), the carbon source material is one or more of nano-carbon powder, nano-graphite, graphene; the iron source material is one or more of commercial nano-iron powder, metal iron powder obtained by hydrogen reduction of nano-scale iron oxide.

4. The method according to claim 1, wherein: In step (1), the molar ratio of iron to carbon in the iron source material and the carbon source material is 2:1 to 0.5:1, preferably 2:1 to 1:

1.

5. The method according to claim 1, characterized in that: In step (1), the particle size range of the iron source material and the carbon source material is 20 to 100 nm, preferably 50 to 80 nm.

6. The method according to claim 1, characterized in that: In step (1), the components of the ball milling tank and the balls are zirconia, the volume of the ball milling tank is 30 to 100 mL, preferably 30 to 60 mL; the mass ratio of the grinding balls to the raw materials is 15 to 35, preferably 20 to 30; the diameter of the balls is 2 to 5 mm, preferably 3 to 4 mm.

7. A preparation method for synthesizing Fe2C by mechanical ball milling according to claim 1, characterized in that: In step (2), the set parameters of the ball mill are: the rotation speed of the planetary disk is 200 to 400 r / min, preferably 300 r / min; the rotation speed of the grinding tank is 500 to 700 r / min, preferably 600 r / min, one cycle of ball milling is 20 to 40 min, preferably 30 min; pause for 5 to 15 min between each cycle, preferably 10 min; the number of ball milling cycles is 500 - 800, preferably 550 - 640; the ball milling mode is reverse rotation.

8. The method according to claim 1, characterized in that, In step (2), the total ball milling time is 200 to 500 h, preferably 270 to 400 h, more preferably 290 to 350 h.

9. The method according to claim 1, characterized in that: In step (3), the mesh number of the standard sieve is 60 to 150 mesh, preferably 80 mesh.

10. The Fe₂C material prepared by the method according to any one of claims 1 - 9.

Citation Information

Patent Citations

  • Pure-phase ε / ε' iron carbide catalyst for Fischer-Tropsch synthesis, its preparation method, and the method for Fischer-Tropsch synthesis.

    CN110339849B

  • Boron-containing iron carbide catalyst as well as preparation method and application thereof

    CN116984008A